Challenges and opportunities for checkpoint blockade in T-cell lymphoproliferative disorders. Issue 1 (December 2016) - Phillips, Tycel; Devata, Sumana; Wilcox, Ryan
Abstract The T-cell lymphoproliferative disorders are a heterogeneous group of non-Hodgkin's lymphomas (NHL) for which current therapeutic strategies are inadequate, as most patients afflicted with these NHL will succumb to disease progression within 2 years of diagnosis. Appreciation of the genetic and immunologic landscape of these aggressive NHL, including PD-L1 (B7-H1, CD274) expression by malignant T cells and within the tumor microenvironment, provides a strong rationale for therapeutic targeting this immune checkpoint. While further studies are needed, the available data suggests that responses with PD-1 checkpoint blockade alone will unlikely approach those achieved in other lymphoproliferative disorders. Herein, we review the unique challenges posed by the T-cell lymphoproliferative disorders and discuss potential strategies to optimize checkpoint blockade in these T-cell derived malignancies.